Physical and Mathematical Modeling of Earth and Environment Processes 3rd International Scientific School for Young Scientists, Ishlinskii Institute for Problems in Mechanics of Russian Academy of Science (Springer Geology, 2018)
This book is the result of collaboration within the framework of the Third International Scientific School for Young Scientists held at the Ishlinskii Institute for Problems in Mechanics of Russian Academy of Sciences, 2017, November. The papers included describe studies on the dynamics of natural system - geosphere, hydrosphere, atmosphere-and their interactions, the human contribution to naturally occurring processes, laboratory modeling of earth and environment processes, and testing of new developed physical and mathematical models. The book particularly focuses on modeling in the field of oil and gas production as well as new alternative energy sources.